Efficiency in family bargaining: living arrangements and caregiving decisions of adult children and disabled elderly parents - Liliana E. Pezzin; Robert A. Pollak; Barbara S. Schone (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper, we use a two-stage bargaining model to analyze the living arrangement of a disabled elderly parent and the assistance provided to the parent by her adult children. The first stage determines the living arrangement: the parent can live in a nursing home, live alone in the community, or live with any child who has invited coresidence. The second stage determines the assistance provided by each child in the family. Working by backward induction, we first calculate the level of assistance that each child would provide to the parent in each possible living arrangement. Using these calculations, we then analyze the living arrangement that would emerge from the first stage game. A key assumption of our model is that family members cannot or will not make binding agreements at the first stage regarding transfers at the second stage. Because coresidence is likely to reduce the bargaining power of the coresident child relative to her siblings, coresidence may fail to emerge as the equilibrium living arrangement even when it is Pareto efficient. That is, the outcome of the two-stage game need not be Pareto efficient.
Keywords: D1; J1; J2; 330; Familienökonomik; Generationenbeziehungen; Kinder; Behinderte; Pflegedienst; Altenheim; Pareto-Optimum; Spieltheorie